DIPG-03. EXCITATORY SYNAPSES BETWEEN PRESYNAPTIC NEURONS AND POSTSYNAPTIC GLIOMA CELLS PROMOTE DIPG PROGRESSION. Issue 2 (22nd June 2018) - Venkatesh, Humsa; Geraghty, Anna; Morishita, Wade; Tam, Lydia; Tirosh, Itay; Regev, Aviv; Vogel, Hannes; Suva, Mario; Malenka, Robert; Monje, Michelle
Abstract: High-grade gliomas represent the leading cause of brain tumor-associated death in children. We have recently discovered that active neurons robustly regulate glioma growth through activity-regulated secreted factors that critically include neuroligin-3. Secreted neuroligin-3, in addition to activating multiple oncogenic signaling pathways, induces glioma cell expression of numerous synapse-associated genes. Here, we report that neuron-glioma interactions include bona fide synaptic communication. Glioma cell expression of synapse-related genes was confirmed at the single cell level in primary glioma samples. Structural synapses between presynaptic neurons and post-synaptic glioma cells were identified by high-resolution confocal and electron microscopy. Voltage clamp recordings from patient-derived DIPG cells xenografted to the CA1 region of the hippocampus demonstrates AMPAR-mediated excitatory neurotransmission between presynaptic neurons and post-synaptic glioma cells with local electrode stimulation of inputs to the CA1 region. Millisecond timescale excitatory post-synaptic currents (EPSCs) were observed in approximately 10% of DIPG cells. A subpopulation of glioma cells exhibit a second electrophysiological profile with longer, 1 sec depolarization in response to neuronal activity. As depolarization of normal neural precursor cells during development affects neural stem cell proliferation, we tested the hypothesis that neuron to glioma synapse-mediated depolarization promotes glioma growth. Using in vivo optogenetic techniques to depolarize patient-derived DIPG cells, we found that DIPG cell depolarization robustly promotes proliferation. These findings define an unexpected integration of glioma cells into neural circuitry, identify excitatory synaptic neurotransmission as a mechanism driving glioma growth and elucidate the previously unexplored potential to target glioma circuit dynamics for therapy of these lethal cancers.